Pattern of ocular morbidity in pediatrics age group in a tertiary centre in western Nepal - Tuladhar, S; Gurung, J.; Poudel, B.; Subedi, N. (Journal of Gandaki Medical College-Nepal, 2019)
Introduction: Ocular morbidities are importantbecause of their impact on child’s development,education and future work. Ocular morbidities in children may not be diagnosed and treated in time due to inability to express their problems which leads to amblyopia by the time they can express it. This study was conducted with an objective to determine the pattern of ocular morbidity in children less than and equal to 14 years of age presenting in the Outpatient Department (OPD) of Gandaki Medical College, Pokhara. Materials/ Methods: This is a cross sectional observational study where we reviewed the profile of all of all patients of age group equal to or less than 14 years entering eye OPD from September 2016 to September 2018 for eye examination. Result: A total of 1471 patients presented to eye department of GMC. The mean age of the patient was 8.25 ±4.24 years among which 57.8% were males and 42.2% were females. Maximum number of the patients were in age group 11 to 14 years (38.1%) while minimum number of the patients were in the age group <1 year(10.6%).Conjunctival disorders (23.9%) was the most common ocular morbidity followed by refractive error in (18.2%), miscellaneous conditions (10.4%), eyelid diseases (8.6%), lacrimal system diseases (7.8%). Conclusion: Thestudy gives a picture and pattern of ocular diseases in pediatrics age group which not only helps in early diagnosis and treatment of ocular diseases but also in decreasing the magnitude of childhood blindness and amblyopia.